The Influence of Career Development and Work Communication on Job Satisfaction with Work Discipline as A Moderating Variable - Febrianto, Muhammad Rizky; Fajrin, Aisyah Maharani (Journal of Management and Digital Business, 2025)
Purpose – This research aims to obtain empirical evidence on the Influence of Career Development and Work Communication on Job Satisfaction with Work Discipline as a moderating variable. Design/methodology/approach This research uses a primary research type. This research was conducted using a questionnaire distributed to employees of PT Suzuki Indomobil and Motor, namely 30 questionnaires distributed via social media. Each questionnaire distributed contains 30 statements to be answered by respondents. From the distribution of questionnaires carried out, 30 respondents provided answers. To obtain the results of this study, the researcher used PLS SEM Version 3.0. Findings – Understanding career development has a positive and significant effect on job satisfaction, work communication has a positive and insignificant effect on job satisfaction, work discipline does not strengthen the relationship between career development and job satisfaction and work discipline does not strengthen the relationship between work communication and job satisfaction. Research limitations/implications – This research focuses on job satisfaction and this study is a unique and rarely found study, where the relationship between work discipline does not strengthen the relationship between career development and job satisfaction and work discipline does not strengthen the relationship between work communication and job satisfaction.